2D Sandwich‐Like α‐Zirconium Phosphate/Polypyrrole: Moderate Catalytic Activity and True Sulfur Confinement for High‐Performance Lithium–Sulfur Batteries. Issue 23 (7th November 2019) - Liu, Ye; Yan, Wenjun; Zhang, Wei; Kong, Wei; Wang, Zhongde; Hao, Xiaogang; Guan, Guoqing
Abstract: Although lithium–sulfur batteries are promising environmentally friendly and low‐cost energy storage devices with high energy densities, many obstacles such as poor conductivity, volume expansion and the "shuttle effect" still limit their large‐scale commercialization. In this work, a 2D sandwich‐like α‐ZrP/polypyrrole (α‐ZrP/PPy) material with a nanosheet structure was designed as a sulfur host. The material can provide unique ion transfer channels for the rapid transfer of Li + ions and catalytically promote the conversion of lithium polysulfides (LiPSs). Moreover, the α‐ZrP nanosheets provides a true covalent anchor for sulfur species, whereas the PPy builds a physical barrier and forms a conductive network for accelerating the electron transport and promoting the electrochemical performance. In addition, the moderate catalytic activity and true sulfur confinement effect of α‐ZrP were confirmed by experiments and theoretical calculations. The α‐ZrP/PPy@S cathode exhibits a highly reversible capacity of 727.2 mAh g −1 even at a high current density of 5 C, offering a novel cathode material for high performance Li–S batteries. Abstract : Welcome to the cell : 2D sandwich‐like α‐ZrP/polypyrrole (α‐ZrP/PPy) nanosheets are designed as a sulfur host material. The material has a remarkably enhanced cycling performance, excellent rate capability, and improved coulombic efficiency owing to the true covalent confinement of sulfur and moderate catalytic activity for the conversion of LiPSs. Such α‐ZrP/PPy@S composites can be applied as promising cathode materials for Li–S batteries.